Moderasi Beragama sebagai Jembatan antara Dakwah Islam dan Pendidikan Kewarganegaraan - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiyavi; Dwi Ajeng Pratiwi; Umi Hanik; Afifa Nur Kholifah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Religious moderation emphasizes balance in understanding religious teachings, so that it can be a bridge in building harmony between Islamic preaching and civic education. This study aims to analyze how religious moderation can be a meeting point between Islamic preaching that is oriented towards strengthening Islamic values and civic education that focuses on the formation of national character. The research method used is a literature study with a descriptive qualitative approach. The results of the study indicate that religious moderation can integrate Islamic and national values through the principles of tawasuth (moderate), tawazun (balanced), i'tidal (fair), and tasamuh (tolerance). Moderation in Islamic preaching helps create an inclusive understanding of religion and respects diversity, while in civic education, religious moderation strengthens nationalist attitudes without eliminating religious identity. Thus, religious moderation plays an important role in building a harmonious, tolerant, and nationally characterized socicty.